Feminist Views on Female Puppeteer's Role in Supporting Cultural Diplomacy - Harini, Setyasih; Hastini, Dite; Arlinda, Silvi Aris (Jurnal Hubungan Internasional, 2026)
This study explores the female puppeteers’ contribution in the Javanese shadow puppetry traditions, framing them as agents of Indonesia’s cultural diplomacy. Most of the work done on cultural diplomacy and soft power has focused on the states and the role of the women performers has been overlooked. Work on cultural diplomacy has largely ignored the feminist perspective, or the performances of the women in the indigenous traditions of the performative arts. This study attempts to fill this gap by using qualitative research methods focused on case study, participatory observation, and document study. To understand the women dalang of Java, this article conducted in-depth interviews with fifteen of them. This study employs soft power theory by Joseph S. Nye and postfeminist theories by Rosalind Gill and Angela McRobbie as the cornerstones of this research. The female puppeteers transform the cultural narratives and export them to culturally inclusive narratives. The study posits that the incorporation of postfeminist agency into the analysis of soft power, allows the theory to move beyond the state centered focus of attraction. The female puppeteers of puppetry are able to transform the patriarchal narratives of puppetry into tools of conscious gender and dialogic diplomacy. They contribute to the perception of Indonesia as a nation that is culturally anchored and inclusive.